THERMAL TIME ACCUMULATION AND HEAT USE EFFICIENCY OF DIRECT SEEDED FINE AROMATIC RICE - A. Matloob; A. Khaliq; A. Tanveer; F. Rasul; A. Wahid (Journal of Animal and Plant Sciences, 2015)
Weeds pose serious threat to success of direct seeded rice (DSR). Cultural practices can alter dynamics of weed-crop competition through alteration of growth and accumulation of thermal time for phenological development. Thermal time accumulation by the DSR crop under different tillage systems, sowing times and durations of weed competition was studied through field experiments during the summer of 2010 and 2011. A commonly grown fine aromatic rice cultivar, Super Basmati was sown on the 15th June and 7th July under zero and conventional tillage, and subjected to different durations of weed competition (10, 20, 30, 40, 50 days after sowing and season long competition A randomized complete block design with the split-split arrangement employing three replications was used. Tillage systems were kept in main plots, while the sowing times and the durations of weed competition were assigned to sub- and sub-sub plots, respectively. The net plot size was 7 m × 2.2 m. Weed free plots were maintained under each tillage system and sowing time for comparison. Thermal time accumulated by DSR between different phenological stages was significantly affected by tillage systems, sowing times, duration of weed competitions, and their interaction. Time taken from sowing to emergence was longer in case of conventional tillage than zero tillage. Crop sown on 7thJuly reached heading stage with comparatively less accumulation of thermal time than 15th June-sown crop. The DSR plots subjected to increasing duration of weed competition needed more heat units to reach heading while thermal time from heading to maturity was decreased. Increasing duration of weed competition reduced heat use efficiency by DSR. In conclusion, late sown DSR crop exposed to weed competition was less efficient in converting accumulated heat units into economic yield. Hence, a DSR crop should preferably be sown by mid-June and weeds must be controlled before 20 DAS to avoid delay in heading and reduction in accumulation of heat units from heading to maturity so that the crop gets an appropriate grain filling period.
Keywords: crop phenology; growing degree days; rice direct seeding; thermal time; tillage systems; weeds